(3TQM HOjYjI GdSjhWis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3Ydj Hf MeRI GdHUQj, CHh GdbGSe,J (B375 (3g` s
(3ChdgG (B:s
(3gPg HOjYjI eOMJ HgG ef hLH Ydi GdNdb GeJOGMg eYGQVkG HgG HOjYjI GdTGYQ Jbi GdOjf CHhHcQ Hf MLI ai GdJhQjI s
(3BNQgG (B:s
(3aJHdjZ PcQi GdCQV HOeGA GdbJdi s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B283 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B83s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B234s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdHdGZIs